PENGARUH KOMPONEN PENGENDALIAN INTERN TERHADAP EFEKTIVITAS PEMBERIAN KREDIT PADA LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN TABANAN - Desak Made Widya Paramitha Swari; Komang Krishna Yogantara; I Putu Agus Atmaja Negara (Journal Research of Accounting, 2021)
This study aims to analyze the influence of the control environment, risk assessment, control activities, information and communication, and monitoring of the effectiveness of credit granting at the Village Credit Institution (LPD) in Tabanan Regency. Data collection methods are done by observation, interviews, and questionnaires. The number of respondents in this study was 50 respondents, in distributing questionnaires using purposive sampling technique. Based on the F test used to test whether the regression model used is fit, if the significant value> α = 0.05 then the hypothesis is rejected, which means the regression model is not fit. If the significant value <α = 0.05, the hypothesis is accepted, which means the fit regression model. F test results show a significant value of 0,000 which means less than 0.05 then the hypothesis is accepted, which means five independent variables namely the control environment (X1), risk assessment (X2), control activities (X3), information and communication (X4) and monitoring (X5), simultaneously have a positive effect on the dependent variable, namely the effectiveness of credit (Y). Likewise with the t test, if a significant level of t α α = 0.05 H0 is rejected and H1 is accepted, if a significant level of t> α = 0.05 H0 is accepted and H1 is rejected. From the results of the t test it can be seen that five independent variables namely the control environment (X1), risk assessment (X2), control activities (X3), information and communication (X4) and monitoring (X5), have a partially positive effect on the dependent variable namely the variable the effectiveness of granting credit (Y) because it has a significantly smaller value of 0.05.